Acute non-immune hydrops fetalis caused by intrauterine echovirus infection. (21st October 2010) - Weitz, J; Das, S
Abstract : We present a case of non-immune hydrops fetalis presenting acutely in the third trimester caused by echovirus infection. The infant required intensive care for over 2 weeks.